Brain natriuretic peptide: new surrogate marker for adequacy of anti-hypertensive treatment - Shrivastava, Mayank; Dhanak, Anoop Kumar; Mathur, Ajay; Sharma, Ramji (International Journal of Advances in Medicine, 2017)
Background: High blood pressure (hypertension) is one of the preventable causes of premature morbidity and mortality. The objective of this study was to assess the difference in mean BNP level at baseline and 3months after start of treatment among newly diagnosed hypertensive cases up to 35 years. Methods: Study was carried out on fifty newly diagnosed hypertensive patients over a period of three months satisfying inclusion criteria. Pre and post treatment BNP level were measured and analysed. Results: 39 (78%) cases out of 50 cases have high BNP in which 5 (10%) cases are in <30 year age group and 34 (68%) cases are in <30 year age group, High BNP level are significant in both age group with p value <0.01. 10 (20%) cases of age <30 year have normal BNP after antihypertensive treatment and 40 (80%) cases of age <30 year out of which 31 (62%) have normal BNP level and 9 (18%) cases have abnormal BNP level after antihypertensive treatment. Mean BNP level in pre antihypertensive treatment is (143.92±25.19) and post treatment is (117.26±11.20), And Mean change in BNP level pre and post treatment is (26.66±20.75) with p value <0.001which is statistically highly significant. Conclusions: Out of many risk factors for raised BNP level, hypertension is also one of the most prevalent factors for raised BNP level. Positive correlation was found between Blood pressure and BNP level reduction after antihypertensive treatment which is highly significant. Thus Potential clinical application of BNP can be expanded, regarding monitoring the adequacy of treatment. By which we can prevent or delay the progression of disease (hypertension).